2016
DOI: 10.1039/c5ra26009d
|View full text |Cite
|
Sign up to set email alerts
|

Facile one-step synthesis of hierarchical porous carbon monoliths as superior supports of Fe-based catalysts for CO2 hydrogenation

Abstract: A versatile strategy involving one-step desilication of coke-deposited spent zeolite catalyst was successfully developed to prepare hierarchical porous carbon monoliths (HPCMs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For FTS catalysts, the active metal iron is easy to form mixed oxides with the oxide support due to strong interaction between them. This may be negative for the reduction of iron and the formation of active phases and thus will lead to low catalytic activity. , For this reason, the support that has weak interaction with active metal will be more effective for FTS such as reduced graphene oxide, activated carbon, N-doped carbon nanotubes, , porous carbon, and silicon carbide . Expanded graphite (EG) is a new type of functional carbon material; it also belongs to the support that has weak interaction with active metal and is beneficial to the formation of the active phase.…”
Section: Introductionmentioning
confidence: 99%
“…For FTS catalysts, the active metal iron is easy to form mixed oxides with the oxide support due to strong interaction between them. This may be negative for the reduction of iron and the formation of active phases and thus will lead to low catalytic activity. , For this reason, the support that has weak interaction with active metal will be more effective for FTS such as reduced graphene oxide, activated carbon, N-doped carbon nanotubes, , porous carbon, and silicon carbide . Expanded graphite (EG) is a new type of functional carbon material; it also belongs to the support that has weak interaction with active metal and is beneficial to the formation of the active phase.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] One of the most desirable fuels obtained from the reduction of CO 2 through the Sabatier reaction (CO 2 + 4H 2 → CH 4 + 2H 2 O) is methane, which is widely used for both domestic and industrial applications. [31][32][33][34] Traditionally, the Sabatier reaction had been thermally driven until Thampi et al reported that it can also be activated photochemically with solar simulated irradiation using Ru/RuO x loaded on TiO 2 . [31][32][33][34] Traditionally, the Sabatier reaction had been thermally driven until Thampi et al reported that it can also be activated photochemically with solar simulated irradiation using Ru/RuO x loaded on TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] The most commonly used catalysts to drive the Sabatier reaction are based on ruthenium [23][24][25][26] and nickel; [27][28][29][30] although several other catalysts have also been investigated. [31][32][33][34] Traditionally, the Sabatier reaction had been thermally driven until Thampi et al reported that it can also be activated photochemically with solar simulated irradiation using Ru/RuO x loaded on TiO 2 . [35] A more thorough investigation of this reaction demonstrated that it was catalyzed photothermally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review article dealing with the intricacy in preparation, electronic properties and catalytic performance of Fe 3 O 4 /carbon nanocatalysts clearly brought out the potential of this catalyst in the conversion of CO 2 to value‐added products . Early works on Fe 3 O 4 /carbon nanocatalysts focused on exploiting the high surface area, excellent heat transfer, and higher thermal and chemical stability of the carbon support . Subsequent research showed that the graphitic carbon supports increased the electron abundance on the metal‐rich sites resulting in a higher activity.…”
Section: Introductionmentioning
confidence: 99%